(Re-)organisation of spatial configurations in visual working memory: The fate of objects rendered relevant or irrelevant by selective attention. Issue 12 (December 2020) - Timm, J David; Papenmeier, Frank
People maintain object locations not as independent absolute positions but based on inter-object relations in the form of a spatial configuration in visual working memory (VWM). Initial evidence suggests that spatial configurations can be reorganised during maintenance; however, this mechanism is not well understood. We report three experiments investigating this reorganisation process. First, we found that directing spatial attention with a retro cue triggers a reorganisation of spatial configurations during maintenance (Experiment 1). Second, we investigated the role of contextual objects rendered either relevant or irrelevant through the retro cue by manipulating the locations of the context at retrieval both within a partial display (Experiment 2a) and a whole display (Experiment 2b). Whereas the similar impairment of memory performance by changing the relevant and global context suggests a complete reorganisation of spatial configurations in VWM, this interpretation was challenged by the observation of impaired memory performance with changes of the irrelevant objects in a whole display that retains the relevant locations. Thus, we suggest that reorganisation should be considered to be the formation of a partial configuration based on the objects rendered relevant by the retro cue in addition to the originally encoded global configuration, with both configurations affecting memory performance.